SOSIALISASI PEMANFAATAN LIMBAH SEKAM PADI MENJADI BRIKET UNTUK WARGA DESA SUMBERURIP - Muhammad Bilal; Yudha Asmara Dwi Aksa; Purnama Putra (An-Nizam, 2023)
The problem experienced by the people of Sumberurip Village is the lack of knowledge and skills to process waste or waste. The people of Sumber Urip Village are divided into several areas of livelihood, but most of the livelihoods of the people of Sumber Urip Village are farmers. The condition of agricultural waste which causes a lot of pollution to the environment, especially rice husk waste or what is commonly known as bran is part of the grain grain in the form of dry, scaly, and inedible sheets, which protect the inside. Rice husk is one of the most beneficial agricultural wastes. However, farmers often think that the husks are agricultural waste that can only be used as fertilizer, ashes, or animal feed. Utilization of rice husk briquettes is one of the solutions in an effort to break down waste that can pollute the environment, and also as an effort to increase understanding, awareness and skills of the people of Sumberurip Village in dealing with waste that can pollute the environment around the village. Based on the problems above, KKN participants are interested in socializing the manufacture of briquettes made from rice husk. Rice husk is widely used as a material for making briquettes.